2008
DOI: 10.1097/brs.0b013e31816f6a2a
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Ketorolac Does Not Predispose to Pseudoarthrosis Following Posterior Spinal Fusion and Instrumentation for Adolescent Idiopathic Scoliosis

Abstract: Ketorolac does not increase the incidence of developing a pseudoarthrosis when used as an adjunct for postoperative analgesia following a PSFI for AIS using segmental spinal instrumentation and iliac crest bone graft. The differences seen here compared with adults may be due to the greater healing potential in these young patients. We recommend utilization of ketorolac after surgery to supplement pain management when necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…6 Although some have cautioned against the use of ketorolac in major orthopedic surgery because of concerns about platelet dysfunction and impaired bone healing, 19,20 there is growing evidence that ketorolac is safe in pediatric orthopedic populations [21][22][23] and spinal fusion populations. 24,25 We found that our pairing of a multimodal pain protocol with early rehabilitation was not associated with an increase in self-reported pain scores, and there is early suggestion that the pain improved on POD 0 and 1. We used self-reported pain scores as both an outcome and a balancing measure.…”
Section: Discussionmentioning
confidence: 84%
“…6 Although some have cautioned against the use of ketorolac in major orthopedic surgery because of concerns about platelet dysfunction and impaired bone healing, 19,20 there is growing evidence that ketorolac is safe in pediatric orthopedic populations [21][22][23] and spinal fusion populations. 24,25 We found that our pairing of a multimodal pain protocol with early rehabilitation was not associated with an increase in self-reported pain scores, and there is early suggestion that the pain improved on POD 0 and 1. We used self-reported pain scores as both an outcome and a balancing measure.…”
Section: Discussionmentioning
confidence: 84%
“…The debate is ongoing, but it has recently been demonstrated that ketorolac did not predispose to pseudoarthrosis in an adolescent idiopathic scoliosis surgical population [23]. Likewise, Dodwell et al [24] reviewed NSAID for postoperative pain treatment in seven high-quality retrospective studies in spine surgery and did not find an increased risk of pseudoarthrosis from shortterm NSAID use during a 12-month follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the effect of NSAIDs on spinal fusion also failed to provide conclusive answers, with some studies showing an inhibitory effect toward fusion while others contradict these findings. [72][73][74][75][76] In vitro and animal studies has shown similar variations in outcome. 64,65 The diversity in study design may have contributed to the lack of consensus, but even studies with identical study parameters sometimes report contradictory findings.…”
Section: Nsaidsmentioning
confidence: 94%